The activation of GPER inhibits cells proliferation, invasion and EMT of triple-negative breast cancer via CD151/miR-199a-3p bio-axis - Huang, Ruiyan (Am J Transl Res, 2020)
Background: Triple-negative breast cancer (TNBC) is an aggressive breast cancer subtype. G protein coupled receptor (GPER), the key player in the intercellular signaling communication, has been verified to participate in tumorigenesis. The present study aims to explore the effects of GPER on cell proliferation, invasion and EMT through CD151/miR-199a-3p bio-axis in TNBC cells. Methods: Total proteins were isolated from TNBC cell lines and GPER expression was determined using western blot assay. CCK-8 assay was used to detect cell viability after being treated with GPER activation. Western blotting and immunofluorescence were applied to measure the level of proteins associated with cell proliferation, angiogenesis and EMT, as well as the Hippo signal pathway. The level of miR-199a-3p and transfection efficiency were evaluated by reverse transcriptase quantitative PCR (RT-qPCR) after being transfected with miR-199a-3p mimics. Cell migration and invasion of TNBC cells were assessed by wound healing and transwell assays. Moreover, luciferase reporter assay was conducted to verify the relationship between CD151 and miR-199a-3p. Results: GPER activation treatment suppressed MDA-MB-231 cell viability, proliferation, migration, invasion, angiogenesis and EMT process. The expression of E-cadherin was increased, but N-cadherin, Vimentin, VEGFA, AngII and CD151 were decreased after GPER activation treatment. Conversely, inhibition of GPER indeed up-regulated CD151 expression. In addition, overexpression of miR-199a-3p supressed cell proliferation, migration, invasion and angiogenesis, as well as EMT process and the Hippo signal pathway. Conclusion: Collectively, the activation of GPER inhibits cells proliferation, invasion and EMT of triple-negative breast cancer via CD151/miR-199a-3p bio-axis. This study provides a novel intervention target for the treatment of breast cancer cells and a fresh idea for the clinical therapy of breast cancer.